(untitled) (Revista do LabDGE - UFF, 2023)
The hospital environment influences the chain of transmission of pathogenic microorganisms linked to the incidence of infections, making cleaning and disinfection (L&D) management measures necessary in order to contribute to patient safety. This study aimed to propose the viability of using the Lean Six Sigma approach in the management and improvement of the hospital terminal hygiene process. Method: Exploratory descriptive research, through a theoretical survey of tools used in the Lean Six Sigma approach. The DMAIC method, was used as a guide for this project hypothesis of management of the process of terminal hygienization of beds of a University Hospital in the city of Rio de Janeiro. Results: In the definition and organization phase of the project, the terminal sanitization process can be mapped through the VSM diagram and by an employee interview instrument during GEMBA. L&D quality assessment tools like fluorescent markers, ATP test and microbiological cultures can serve as pre and post indicators for possible improvement interventions. Tools such as: Current Reality Tree; GUT matrix; Prioritization matrix and 5W2H plan have proven to be good choices for the analysis and improvement phases. Finally, audits, visual and participative management, indicator reports for maintenance of actions can be done. Conclusion: The application of the DMAIC method of the Lean Six Sigma approach in hospital cleaning processes proved to be objective and feasible according to the proposed method, presenting itself as an alternative basis for future projects in the area.